Rheumatic Fever and Antibody Response to Group A Streptococcal Infections - Neupane, Ganesh Prasad; Makaju, R; Koju, R (Nepalese Heart Journal, 2017)
Rheumatic fever is non-suppurative sequel of group A streptococcal infection. It is a multifocal inflammatory disease, affecting primarily the heart, joints, skin and central nervous system occurring in 0.1% to 3% after untreated pharyngitis. It was a major cause of death and a common cause of chronic structural heart disease in children until 1960. It has declined in developed countries due to advent of penicillin and improved social conditions. Rheumatic fever is very common disease among children in developing countries till date. Rheumatic fever and its clinically significant sequel, rheumatic heart disease, continue to be a major health problem in developing countries like Nepal. Rheumatic fever is still a major cause of death and heart disease.